DEVELOPMENT OF LEGAL EDUCATION IN THE ACTIVITIES OF LEGAL CLINICS AND THE APPLICATION OF INFORMATION TECHNOLOGIES DURING THE IMPLEMENTATION OF LEGAL EDUCATIONAL MEASURES - Письменна, Олена (Modern engineering and innovative technologies, 2025)
The article examines the development of legal education – a set of activities carried out by students-consultants of the legal clinic, the goal of which is to improve the legal culture and consciousness of citizens. Legal education is examined as a proces